Different type of periodontitis and gingivitis in patients with major thalassemia comparing to ‎healthy people - Mohadeseh Arabsolghar‎ (Journal of Oral Health and Oral Epidemiology, 2015)
BACKGROUND AND AIM: Iran is located on the thalassemia belt and has the highest prevalence rate of patients compared to the general population in the world. This investigation was performed to determine the prevalence of gingivitis and periodontitis in thalassemia patients in comparison to healthy people and evaluate the relationship between periodontal disease and age, gender, splenectomy and dosage of desferal.